Extracurricular Public Speaking Activities on the Development of Self-Confidence of Elementary School Students - Yovita Anastasya Aprilia; Minsih (Elementary Teacher Education Program, Majalengka University, 2024)
Extracurricular activities are efforts made by Muhammadiyah PK Baturan Elementary School to support the talents of its students, one of which is extracurricular public speaking activities. Researchers are interested in discussing extracurricular public speaking activities because they are rarely found in elementary schools. This research uses a qualitative case study method. Extracurricular public speaking activities address various aspects of public speaking, including acting as a host, telling stories in class, and presenting in front of a camera. Although most students showed self-confidence, some students needed intensive guidance from the extracurricular teacher to be confident. The purpose of the study was to describe extracurricular public speaking activities to develop students' confidence level for the better. The result of this study is that extracurricular public speaking activities have high enthusiasm from students so that many students participate in extracurricular activities with a sense of interest in developing self-confidence through material activities provided by extracurricular teachers.